Two-Sided Learning, Labor Turnover and Worker Displacement - Gerard A. Pfann; Daniel S. Hamermesh (Institute for the Study of Labor (IZA), 2001)
We construct a general dynamic structural model of two-sided learning between a firm and its workers. We estimate an empirical version of the model using personnel data from Fokker Aircraft that cover the path of layoffs and quits through its bankruptcy. We find that the firm learns about its workers? loyalty (demonstrating the role of information in repeated cooperative principal-agent relationships). There is no evidence that workers learn (consistent with earlier empirical results on American workers). The type of data that we use also generates information on the value of learning and on whether and how the characteristics of workers who remain until the firm?s death differ from those of all affected workers. It thus allows us to measure the increases in the firm?s value from learning about its workers? behavior and to infer the extent of biases in estimated losses from displacement from samples restricted to displaced workers.
Keywords: J33; J63; 330; Learning; turnover; displacement; Lernen; Arbeitsbeziehungen; Kündigung; Theorie; Luftfahrtindustrie; Niederlande